Acting Out a Memory-based Game in Classroom: A Study on Elementary School Students’ English Proficiency - Wahono, Suparwoto Sapto; Ahmad, Sayyidah Indah Nadella; Hidayah, Putri Nuril; Putri, Faradifah Prilia (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
English lessons in Indonesia still have various problems as it serves as a foreign language (EFL). This research aimed to solve elementary students problems in learning English by introducing the memory match game technique. Conducted at Madrasah Aliyah Al-Hidayah in Jember, the study utilises Classroom Action Research (CAR) methodology, emphasising a cyclical process of planning, acting, observing, and reflecting. The collaborative approach involves the researcher as the English teacher employing the memory match game, with the real English teacher serving as an observer. Results indicate that 71.43% of class IV students actively participated in the game, showcasing engagement without seeking assistance, while 28.57% appeared less active. The study highlights the potential efficacy of the memory match game technique in early English language education and calls for continued research to enhance teaching and learning practices.